English Teacher Educators’ (Etes’) Autonomous Learning Perceptions in Tertiary Level of Riau Province - Khulaifiyah, Khulaifiyah; Widiati, Utami; Anugerahwati, Mirjam; Suryati, Nunung (Journal of English Language and Education, 2023)
The idea of autonomous learning is correlated with adult education, therefore, the ETEs views about this idea is being focused to bring about positive academic behaviors for the learners’ successful in language learning and to set autonomous personal quali-ties in terms decision making-ability, learner independency, psychology of learning and level of learner autonomy. With the help of NVivo 12 Software, this qualitative study investigates English teacher educators' (ETEs’) perception on autonomous learning in tertiary level of Riau Province. There were 6 ETEs agreed to be active informants and participated in interviews and observations. Structured interviews were in charge of taking primary data. Meanwhile observations become supportive data. After the data was collected and transcribed, the researchers identify, classify, and categorize the essential data from the interviews, create the coding and run into matrix coding in Nvivo 12 software. The findings inform us that they agreed with the importance of decision making for the EFL learners under the student-centered learner approach; yet, they perceived that learner independency was still low, meanwhile, for the psychology of learning, the ETEs’ still have little attention since  the level of learner autonomy was still lied on the amount of instructions and practices. In sum up, the ETEs' perceived autonomous learning lexically as a life skill that language learners, particularly adult learners should poses as a language learner identity. However, the ETEs’ still insist to assist learners to attain learning success while making them expert in decision- making.